Eficiência da inoculação das sementes com Azospirillum brasilense no rendimento e no potencial fisiológico das sementes de trigo - Piccinin, Gleberson Guillen (2012)
The seed inoculation with bacteria of the genus Azospirillum have been held onvarious grasses with little results broadcast. The objective this work was to evaluate the efficiency of seed inoculation with Azospirillum brasilense on the agronomic performance and seed quality of wheat. It was conducted experiment design in randomized blocks with six replications arranged in a factorial (3 x 3 x 2). The factors were three nitrogen doses (zero, half and full dose); seeds inoculation with A. brasilense (no inoculant, liquid inoculant and peat-based inoculant); bioregulator 2 doses (0 and 250 mL ha-1) applied at tillering in two crop seasons (2010 and 2011). The data were subjected to analysis of variance over and were performed the necessary developments of the interactions. At the point were harvest, we evaluated the agronomic performance: number of grains by ear, weight of a thousand seeds, hectolitre weight and yield, also, the seeds was performed using the following tests: germination (first count and final count), cold, accelerated aging, electrical conductivity, protein and nitrogen content. It is inferred that Azospirillum brasilense is effective in accomplishing partial nitrogen fixation supplemented with nitrogen, the yield is positively influenced by nitrogen associated with inoculation of the type of inoculums, the bioregulator do not increase the quality of wheat seeds when applied at the beginning of tillering, but increases protein content in seeds.